PENGARUH PERILAKU PEMIMPIN TERHADAP KEYAKINAN BAWAHAN PADA KEPEMIMPINAN TRANSFORMASIONAL: SUATU PENDEKATAN MODEL SYNCRETICAL - Linawati, Linawati (KINERJA, 2004)
This research is intended to analyze the influence of leader behavior on follower belief in transformational leadership based on syncretical model of charismatic/transformational leadership. There are three problems to discuss on this research: (i) What the displays empathy and dramatizes the mission of leader behavior has influence on the inspiration of follower?, (ii) What the projects self-assurence and enhances the leader’s image of leader behavior has influence on the awe of follower?, (iii) What the assures followers of their competency and provides followers with opportunities to experience success of leader behavior has influence on the empowerment of follower?The number of the respondent is 119 graduate students of Magister Management Program taken from three (3) state and private universities in Jogjakarta. The questionnaire developed by Behling and McFillen (1996) was used to collect the data. Eighteen (18) items are used to measure the variable of leader behavior and fifteen (15) items are used to measure the variable of follower belief. The data were analized by Multiple Regression Analysis.The result of this study indicate that: (i) the displays empathy of leader behavior has a positive and significant influence on the inspiration of follower, while dramatizes the mission of leader behavior has no influence on the inspiration of follower, (ii) projects self-assurence and enhances the leader’s image of leader behavior has a positive and significant influence on the awe of follower, (iii) assures followers of their competency and provides followers with opportunities to experience success of leader behavior has a positive and significant influence on the empowerment of follower.Keywords: Leader Behavior, Follower Belief, Transformational Leadership, Syncretical Model of Charismatic/Transformational Leadership.